2019
DOI: 10.3390/ma12203338
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Numerical Approach for Analyzing the Residual Stresses in AISI 301LN Stainless Steel Induced by Shot Peening

Abstract: Shot peening is one of the most famous mechanical surface treatments to improve fatigue performance of metallic components, which is attributed to high amplitude compressive residual stresses. A numerical approach is developed to analyze the residual stresses in 301LN metastable austenitic stainless steel by shot peening. The material behavior is described by a proposed constitutive model in which strain-induced martensitic transformation, isotropic hardening and kinematic hardening effects are taken into acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Finally, the residual stresses after shot peening presented S-shaped distribution along the thickness direction. The similar trend was observed in shot peening simulation of steel, in work by Dieng et al [ 21 ], Zhou et al [ 27 ], and Wu et al [ 29 ]. The literature indicated that the surface compressive stresses were introduced by the elastic deformation, whereas the internal compressive stresses were introduced by the plastic deformation, and their magnitudes were mainly related to the material being shot peened [ 23 ].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Finally, the residual stresses after shot peening presented S-shaped distribution along the thickness direction. The similar trend was observed in shot peening simulation of steel, in work by Dieng et al [ 21 ], Zhou et al [ 27 ], and Wu et al [ 29 ]. The literature indicated that the surface compressive stresses were introduced by the elastic deformation, whereas the internal compressive stresses were introduced by the plastic deformation, and their magnitudes were mainly related to the material being shot peened [ 23 ].…”
Section: Resultssupporting
confidence: 84%
“…The results indicated that the residual compressive stresses are proportional to the shot peening speed, and the compressive stress depth increases with the increase of coverage. Zhou et al [ 27 ] proposed a numerical method to analyze the residual stresses introduced by shot peening, and the experiment verified the validity of the model. Liu et al [ 28 ] used SPH method to simulate shot peening to eliminate welding residual stresses.…”
Section: Introductionmentioning
confidence: 95%
“…Various surface modification techniques can be employed to enhance the properties of 301LN. SP has a positive impact by inducing a compressive stress layer that improves its fatigue strength, wear resistance, and resistance to stress corrosion cracking [161,162]. These effects make SP a valuable surface modification technique for enhancing the mechanical performance and durability of 301LN components [163].…”
Section: Wear Resistancementioning
confidence: 99%
“…However, not all disc spring manufacturers quality controls for the steels they use, or cover the product cost of alloying. The other approach of great interest is to produce residual compressive stress in the surface by shot peening [9]- [11]. However, there are some adverse effects on the fatigue strength caused by excessive shot peening, such as an increase in surface roughness and an uncontrollable stress distribution in disc spring surface [12], [13].…”
Section: Introductionmentioning
confidence: 99%